Rating Assessment of the Competitiveness of Banks of the Republic of Belarus - D. S. Shumsky; Ch. A. Zabrodskaya; O. A. Sosnovsky (Цифровая трансформация)
The article proposes an original system of indicators, including financial performance indicators, digital development efficiency indicators, and bank competitiveness indicators. On the basis of systematic and integrated approaches, index methods and the formed system of indicators, a methodology for rating the competitiveness of banks in the Republic of Belarus has been developed. A correlation analysis of competitiveness indices was carried out. The results of the assessment are presented and recommendations for their practical use are given. Based on the results of the assessment, the top 5 banks were identified in terms of such indicators as the Digital Development Efficiency Index and the Bank Competitiveness Index, and the reasons that led to the leadership of these banks were identified. On the basis of the study, a methodology for assessing the effectiveness of development and competitiveness of banks in the Republic of Belarus was formed, which takes into account the peculiarities of the functioning and development of Belarusian banks.